The reputation-management industry and the prospects for a "right to be forgotten" in the US. Issue 1 (2nd January 2017) - Medeiros, Ben
Abstract: Online speech platforms present novel risks to privacy and reputation. There are situations in which unique kinds of harm can indeed occur but where the law applies imperfectly. Yet legal expansions like the European "Right to Be Forgotten" would contradict several well-established tenets of American free speech law. This paper argues that the reputation-management industry (RMI) represents one set of solutions in the absence of an American Right to Be Forgotten. The RMI counsels assiduous self-monitoring, search engine optimized promotion of one's own preferred content, and negotiation for voluntary removal by content hosts. This approach arguably helps to address the informational distortions than can be created by true accounts of unseemly conduct and mob-like expressions of vitriolic opinion online. It likewise helps to mitigate the concern that readers will form inaccurate or unduly harsh judgments based on cursory examination of search results.The RMI thus in some ways addresses the underlying gaps between legal protection and perceived harm in a manner that accords better with the emphasis on "counterspeech" in the American free speech tradition. At the same time, the article concludes by addressing some limitations that are necessary to keep the industry from threatening free-speech principles itself.